Research on personality determinants of athletes` mental exhaustion during the ongoing COVID-19 pandemic - Popovych, I.; Halian, I.; Halian, O.; Nosov, P.; Zinchenko, S.; Panok, V. (Journal of Physical Education and Sport, 2021)
The research presents theoretical substantiation and correlation analysis of the factors causing emotional indifference in athletes with different levels of mastership, participating in individual and team sports (n = 180). The purpose is to carry out empirical research on athletes` personality traits helping overcome mental exhaustion and prevent form emotional indifference.Research methods: correlation analysis, valid and reliable psycho-diagnostic instruments. The research was conducted during the ongoing COVID-19 pandemic and made it possible to find out a number of regularities. Results. The development of mental exhaustion in athletes is determined by a different level of manifestation of personality traits and their correlation in the structure of personality: anxiety, self-esteem, the level of aspirations, locus of control and motivation for achieving success and avoiding failures. The study shows that significant differences between the level of aspirations and self-esteem in the men (r = .38**), high anxiety in the men and women correlating with the integral index of mental exhaustion (r = .28**; r = 36**) mostly contribute to mental strain in many athletes. It finds out that the events of their personal lives become a factor of mental exhaustion provided that external locus of control prevails. This trait is pronounced in the athletes - Masters of team sports (r = .34**). The research determines that a low level of mental exhaustion in the athletes engaged in team sports is a consequence of the significance of social support (r = -.38**). High requirements for demonstrating success cause mental strain for the male athletes that increases probability of their mental exhaustion. Conclusions. The obtained results operationalize the process of solving the problems of professional training for athletes. Understanding the essence of mental exhaustion allows solving the problem of emotional indifference in athletes. Research on the role of emotional intelligence in the structure of athletes` mental exhaustion is considereds to be very promising.